'I still feel lost……..in those wonderful event memories': enablers of event and destination image. (12th April 2022) - Mandal, Santanu; Bhowmik, Pratyush; Panicker, Deepthi R.; Das, Payel
While studies have explored the importance of destination image in enhancing tourism, there have been limited investigations regarding event image and destination from a nostalgia perspective. In this study, we explore the role of nostalgia, cultural connection, and positive word of mouth in shaping event and destination images. Furthermore, the study explores how event and destination image thus developed shapes intention to recommend and revisit intentions for tourists. The study executed a survey from 159 individuals having positive memories of an event at a destination. The completed responses were analysed using partial least squares in ADANC0 2.2. The partial least squares results show that nostalgia, cultural connections, and positive word of mouth significantly influence the image of events and destinations. Furthermore, the image of events and destinations has a significant influence on the intention to recommend and to visit the destination again.